THE ROLE OF ISLAMIC BOARDING SCHOOLS IN BUILDING SPIRITUAL VALUES, NATIONAL VALUES AND CULTURAL VALUES IN INDONESIA - Mirhabun Nadir (Universitas Islam Malang, 2021)
Reading pesantren in the modern paradigm is a very urgent and interesting study. Because, we can know the extent of the strength of pesantren in facing the horizons of the social life of the Indonesian people. It can also be faced with criticisms that arise against pesantren. The criticism is in the form of its credibility as a traditional Indonesian educational institution in dealing with technological advances and responding to contemporary problems that are emerging and must be immediately found.Islamic boarding schools have multiple roles that other educational models do not have, the role of pesantren covers various basic aspects of the life of the Indonesian nation, providing values that further strengthen the existence of the Unitary State of the Republic of Indonesia, the values given by pesantren can be categorized into three kinds of values; Spiritual Values, National Values and Cultural Values.Keywords: Pesantren, Value, Spiritual, Nationality, Culture.